Integration of Cultural Elements in Professional Training for Choreographer–Teachers of Traditional Chinese Dance - XiangYun, Qian; Saearani, Muhammad Fazli Taib (Global Journal of Social Learning, 2025)
Interest in traditional Chinese dance education has weakened due to the dominance of Western dance, industry fragmentation, and limited cultural integration in professional training. This study examines how cultural elements—historical context, folklore, cultural values, customary practices, and aesthetic principles—are embedded in the training of choreographer–teachers of traditional Chinese dance. A qualitative case study was conducted in three major institutions (Beijing Dance Academy, Shanghai Theatre Academy, and Minzu University of China) involving 12–15 choreographer–teachers. Data were collected through semi-structured interviews, participant observation, and curriculum document analysis, and analysed thematically using Cultural–Historical Activity Theory (CHAT) and Culturally Responsive Teaching (CRT). Findings show that cultural elements are integrated through demonstrative techniques, traditional narratives, contextual exercises, and adapted movements that ensure student safety while retaining cultural and aesthetic authenticity. These strategies strengthen social cohesion, artistic creativity, learner motivation, and cultural identity, while reinforcing the institutions’ roles as key sites of cultural transmission. Major challenges include limited resources, shortages of qualified instructors, resistance to innovation, cultural sensitivities, and performativity pressures. Theoretically, cultural integration operates as a mediating artefact within CHAT and supports culturally responsive pedagogy through CRT, enabling a balanced negotiation between innovation and tradition. The study recommends developing adaptive and sustainable training models that integrate physical safety, artistic creativity, and the digital preservation of cultural materials to broaden access and support the long-term continuity of traditional Chinese dance.